Pelatihan Dasar dan Aplikasi Internet of Things di Sekolah Menengah Atas Negeri 6 Metro Lampung - Mege, Christio Revano; Suaif, Ahmad; Putra, Septia Eka Marsha; Khoirunisa, Vera; Siregar, Sefrani IG; Saputra, Alvin; Ramadhani, Sofia Nur (GOTAVA Pengabdian Kepada Masyarakat, 2025)
Metro 6 State Senior High School is one of the schools that produces the best graduates in Metro City. Learning at this school strives to utilize the latest technology that is in accordance with the needs of the times. One technology that has not been taught at this school is Internet of Things technology. The Internet of Things (IoT) is a concept that refers to a network of physical devices connected via the internet, which are able to exchange data without requiring human-to-human or human-to-computer interaction. In the context of IoT, "physical devices" can include various types of objects, such as sensors, vehicles, household appliances, medical devices, and many more. Metro 6 State Senior High School students do not yet have an understanding of IoT theory and applications. This PKM activity introduces IoT technology through knowledge dissemination and practical assistance for IoT applications in simple applications such as turning on lights via smartphones. The results of this PKM activity are that students' knowledge of IoT theory and applications has increased by more than 100%, as shown by the results of the pre-test with an average score of 39.41 increasing to 80.59 in the post-test. In addition, students are also able to practice turning on lights via IoT-based smartphones. In addition, students of SMA Negeri 6 are facilitated with esp32 microcontrollers, relays and other tools that support the sustainability of IoT practical activities at this school.